Knowledge of scope of oral and maxillofacial surgery amongst medical students at a tertiary hospital in Kathmandu, Nepal - Panthee, Anuja; Pokhrel, Prenit; Panthee, Asmita; Khapung, Anju (Journal of Kathmandu Medical College, 2023)
Background: Diagnosis and surgical treatment of varieties of traumatic, pathologic, functional, and aesthetic disorders of stomatognathic system are included in the scope of oral and maxillofacial surgery (OMFS). Although this speciality plays a significant part in dentistry and medicine; dental and medical professionals still do not fully comprehend the exact depth.Objectives: To understand the level of knowledge amongst medical students of different levels, to promote the scope of OMFS among health care communities, and establish a fair understanding of the speciality’s contribution.Methods: This questionnaire based descriptive, cross-sectional survey was done on purposive sampling technique. Data were collected from 2022 October to 2022 December among medical students and interns of Nepal Medical College via questionnaire after receiving institutional ethical clearance. Data were entered, coded, and edited using Microsoft Excel 2010 and analysed using SPSS v.20. Descriptive statistics are presented in frequency, percentage, and mean.Results: A total of 254 study participants were included of which 149 (58.66%) were male and 105 (41.34%) were female. Of all, 99 (38.98%) were first year medical students, 80 (31.50%) were second year students, and 75 (29.53%) were interns. Mean knowledge score in preclinical students was 6.27 ± 1.73 and 7.12 ± 1.85 in interns. The result shows adequate knowledge for both groups.Conclusion: Findings of this study assesses the level of knowledge of medical students at a tertiary hospital which will help to highlight the need for awareness and education regarding OMFS, promoting its development, contribution, and impact among the health care professionals.